A 4-year randomized trial comparing three outreach interventions to promote screening mammograms. Issue 2 (23rd May 2018) - Luckmann, Roger; Costanza, Mary E; White, Mary Jo; Frisard, Christine F; Rosal, Milagros; Sama, Susan; Landry, Michelle R; Yood, Robert
Abstract : The authors document the process of implementing a mammography reminder system in a group practice. Women not responding to a mailed reminder were more likely to schedule a mammogram during a simple reminder call than during a call that offered counseling. Abstract: As population health has become a focus of health care payers and providers, interest has grown in mail, phone, and other forms of outreach for improving population rates of cancer screening. Translational research is needed to compare the effectiveness and cost of low- and high-intensity behavioral outreach interventions for promoting cancer screening. The purpose of the article is to compare the effectiveness in promoting biannual mammograms of three interventions delivered over 4 years to a primary care population with a high baseline mammography adherence of 83.3%. We randomized women aged 40–84 to reminder letter only (LO arm), letter + reminder call (RC arm), and two letters + counseling call (CC arm) involving tailored education and motivational interviewing. Mammography adherence (≥1 mammogram in the previous 24 months) at four time points was determined from insurance claims records. Over 4 years, 30, 162 women were randomized. At the end of 4 years, adherence was highest in the RC arm (83.0%) compared with CC (80.8%) and LO (80.8%) arms ( p = .03). Only 23.5% of women in the CC arm were reached and accepted full counseling. The incremental cost per additional mammogram for RC arm women was 30.45 over the LO arm cost. A simple reminder call can increase screening mammogram adherence even when baseline adherence is high. Some more complex behavioral interventions delivered by mail and phone as in this study may be less effective, due to limited participation of patients, a focus on ambivalence, lack of follow-up, and other factors.